PENJAMINAN MUTU PENDIDIKAN DI MADRASAH DENGAN METODE QUALITY FUNCTION DEPLOYMENT - Rohman Rohman; Nilna Milhatan Nasihah; Anas Tri Ridlo Dina Yuliana (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: This mini research describes the concept of education quality assurance in madrasa and Quality Function Deployment method in viewing assessment, needs, and expectation of students in MAN Yogyakarta 1 referring to eight National Education Standards. Research method uses quantitative approach, that is by calculating data assessment, needs, and expectation of students based on House of Quality matrix and calculating results of students’ statistical appraisal toward eight education standards by using software application SPSS version 22 in discerning students’ satisfaction toward education process are being run in madrasa. The results show that assessment aspects, needs, and expectation of students based on calculation of House of Quality matrix are the desire to obtain the worship stuff facility in the form of mukena and its place in the mosque, the availability of fan or air conditioner in each class, refinement and addition of sports field, equipments in the laboratory in the form of a computer. Whereas for education standards of content and process in madrasa, majority of students expect learning methods can be further developed with more interesting methods that are not boring for students. In addition, the calculation results through SPSS show the total number of students who become respondents as many as 57 students. Of the total, 39 students gave good or high appraisal toward education process with the percentage of 68,4%, and the rest 18 students gave less good or low rating with the percentage of 31,6%. Based on class, class XII grade with the number of 33 respondents, 23 of them gave good appraisal of 69,7% and the remaining 10 students gave poor appraisal of 30,3%. While class XI grade with the number of 24 respondents, 16 of them gave good appraisal of 66,7%, and the remaining 8 students gave less good or low appraisal of 33,3%. Keywords: Penjaminan Mutu Pendidikan, Metode Quality Function Deployment.